FLINTA to the Front! German Punk and Its Problem with Sexism (KULT_online, 2023)
The German punk scene has a problem with sexism. Men play in the bands, men slam-dance in front of the stages and men sexually assault the non-male punx at punk shows and beyond. With their anthology Punk as F*ck, punx-turned-editors Diana Ringelsiep and Ronja Schwikowski want to set something against this – namely 50 non-male perspectives on the German punk scene. The outcome is a compilation of 50 texts that are as shocking as they are insightful and as relevant as they are worth reading.